If I didn't have HIV, I'd be dead now: illness narratives of drug users living with HIV/AIDS. - Mosack, Katie E; Abbott, Maryann; Singer, Merrill; Weeks, Margaret R; Rohena, Lucy (Qualitative health research, 2005)
The purpose of this study is to illuminate the experiences of lower income, urban, HIV-positive drug users. The authors asked 60 participants about HIV risk behaviors, the impact of HIV on their lives, religious beliefs, life plans, relationships, and work-related issues both prior to and since diagnosis. They developed a theoretical framework based on illness narratives and ambiguous loss theories. Themes pertaining to both physical and emotional or spiritual dimensions were located within Benefit, Loss, or Status Quo orientations. The findings contribute to researchers' understanding of the HIV/AIDS illness experiences among the very marginalized and have important implications for physical and mental health care professionals working with HIV-positive drug users.
Keywords: Acquired Immunodeficiency Syndrome; Adult; Antiretroviral Therapy, Highly Active; Connecticut; Female; HIV Infections; Humans; Interviews as Topic; Life Change Events; Male; Middle Aged; Narration; Qualitative Research; Risk-Taking; Substance Abuse, Intravenous; Vulnerable Populations